2016
DOI: 10.1002/smll.201602163
|View full text |Cite
|
Sign up to set email alerts
|

Rapid One‐Pot Preparation of Large Freestanding Nanoparticle‐Polymer Films

Abstract: 2D arrays of metal nanoparticles formed at liquid–liquid interfaces have been fixed in situ to a thin polymer support to create freestanding large (cm2) composite films where the particles remain exposed rather than being trapped within the polymer. Applications of these flexible robust 2D nanoparticle arrays as sensors, thin film conductors, antimicrobial coatings, and dip‐in catalysts are shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 33 publications
2
63
0
Order By: Relevance
“…The key component is a recently reported new class of flexible SERS substrates, surface exposed nanoparticle sheets (SENS), which are composed of 2-dimensional arrays of NPs physically anchored onto a flexible polymer support (Fig 1a and b) [22]. In these films the nano-gaps are still exposed and accessible, since the particles are only partly submerged into the polymer but the polymer backing makes them physically robust and able to withstand the pressure required to force solid materials into plasmonic enhancing regions to achieve significant signal enhancements (Fig 1b).…”
Section: Proof-of-principle Studiesmentioning
confidence: 99%
“…The key component is a recently reported new class of flexible SERS substrates, surface exposed nanoparticle sheets (SENS), which are composed of 2-dimensional arrays of NPs physically anchored onto a flexible polymer support (Fig 1a and b) [22]. In these films the nano-gaps are still exposed and accessible, since the particles are only partly submerged into the polymer but the polymer backing makes them physically robust and able to withstand the pressure required to force solid materials into plasmonic enhancing regions to achieve significant signal enhancements (Fig 1b).…”
Section: Proof-of-principle Studiesmentioning
confidence: 99%
“…Ideally, what is required is a simple method that can be used to arrange various types of NPs into robust 3D materials which are strong enough for routine handling while retaining their nanoproperties. Previously, we have shown that charged colloidal NPs of various morphologies and material compositions can be induced to self-assemble into densely packed 2D arrays at the LLI using oppositely charged promoter ions to provide charge screening [20,21]. In the current work we extend our approach for assembling 2D arrays to the assembly of densely packed interfacial 3D arrays, this is then combined with in-situ polymer deposition to form suspensions of NP/polymer hybrid materials consisting of exposed and densely packed NP surface layers fixed on solid polymer micro-particle cores.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, this group has reported a method for preparing robust, flexible 2D MeLLF films involving their deposition on a thin polymer film bed [10]. In these nanoparticle polymer films, or 'Surface-Exposed Nanoparticle', i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In these nanoparticle polymer films, or 'Surface-Exposed Nanoparticle', i.e. SEN, plastic films, the nanoparticles are partially embedded in the polymer film, usually polystyrene (PS), but other polymers have been used [10]. Thus, Au-or Ag-SEN plastic films have been used to catalyse reactions or promote the detection of analytes by SERS [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation